2018
DOI: 10.1002/lno.11066
|View full text |Cite
|
Sign up to set email alerts
|

The role of double diffusion for the heat and salt balance in Lake Kivu

Abstract: Double diffusion in lakes and oceans can transform vertical gradients into staircases of convectively mixed layers separated by thin stable interfaces. Lake Kivu is an outstanding double‐diffusive natural laboratory with > 300 such steps over the permanently stratified deep basin. Here, we use 315 microstructure profiles (225 measured in Rwanda and 90 in the DRC) to shed light on the heat and salt balances of Lake Kivu. Comparing profiles from 2011 and 2015 reveals warming of 8.6 mK yr−1 below 80 m depth and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Powell Lake in British Columbia is the most prominent representative of this category [24,36]. With three and four density-relevant water constituents, there are examples of lakes showing triple-diffusion [23], such as the present study, and quadruple-diffusion, such as Lake Kivu [33]. More DD-type lake examples are reviewed in Wüest et al [42].…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Powell Lake in British Columbia is the most prominent representative of this category [24,36]. With three and four density-relevant water constituents, there are examples of lakes showing triple-diffusion [23], such as the present study, and quadruple-diffusion, such as Lake Kivu [33]. More DD-type lake examples are reviewed in Wüest et al [42].…”
Section: Introductionmentioning
confidence: 80%
“…Double-diffusive stratification is generally rare in lakes, because usually T decreases and S increases with depth leading to classical diffusively stable water columns. However, prominent exceptions of DD-developing stratification were found above former salt depositions, such as in Lake Vanda [9,10] and several other lakes in the Antarctic Dry Valley [34,35], or over volcanic underground, such as in Lake Kivu [18,33]. Another set of DD-type lakes can be found on the Norwegian and Canadian West Coast, where Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying equation yields Pe = 3.4 × 10 3 , and thus, JbPe = 3.1 × 10 −10 W kg −1 . Recently, Sommer et al () reported an average dissipation within the MLs of Lake Kivu of 1.5 × 10 −10 W kg −1 . The same study considers a mixing efficiency of 0.8, and thus, a J b = 1.9 × 10 −10 W kg −1 , which is in good agreement with JbPe.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, analogous loosely tethered profilers mounting fast-response thermistors are typically operated at profiling speeds between 0.1 m s −1 and 0.4 m s −1 (refs. 12 , 21 , 23 , 67 , 68 ). However, we found that the a profiling speed of ~0.75 m s −1 was a reasonable compromise between optimizing shear and fast-response thermistors performance: the ability of shear probes to be used in medium- to high-energy environments (i.e., ε > 5 × 10 −10 m 2 s −3 ) compensated the time response limitations of the FP07 sensors.…”
Section: Technical Validationmentioning
confidence: 99%